On-chip beam steering through reprogrammable integrated coding metasurfaces - Muhammad Shemyal Nisar; Shahid Iqbal; Sai-Wai Wong (Results in Physics, 2023)
Coding metasurfaces have found many applications in free space optics, but have not been used for integrated photonic applications. This can partly be attributed to the lack of implements to usefully implement such a framework in practice. The advent of low-loss phase change materials such as Sb2S3 has changed this by enabling the implementation of reprogrammable integrated metasurfaces. This manuscript presents Sb2S3 based 1-bit and 2-bit coding metasurfaces that can potentially also be practically implemented. These metasurfaces can achieve functionalities such as beam focusing, beam splitting, and beam steering through the rearrangement of the material phase of Sb2S3. This can find potential applications in numerous fields including integrated photonic computational platforms.